2010
DOI: 10.4141/cjss09052
|View full text |Cite
|
Sign up to set email alerts
|

Pedogenic, mineralogical and land-use controls on organic carbon stabilization in two contrasting soils

Abstract: S. S. 2010. Pedogenic, mineralogical and land-use controls on organic carbon stabilization in two contrasting soils. Can. J. Soil Sci. 90: 15Á26. Organo-mineral complexation in soils is strongly controlled by pedogenesis, but the mechanisms controlling it and its interaction with cultivation are not yet well understood. We compared the mineralogy and quality of organic carbon (C) among organo-mineral fractions from two soils with contrasting pedogenic origin. Sequential density fractionation (SDF; using 1.6, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
13
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
5
13
2
Order By: Relevance
“…However, in the semiarid soils of the studied transect, particulate OC contributed < 10 % of bulk OC, while mineral-bound OC accounted for > 90 % (Table 3). This contrasts with observations from the steppe soils (mostly Chernozems) of European Russia (Breulmann et al, 2014;Kalinina et al, 2011), Canada (Plante et al, 2010), and China (Steffens et al, 2010) in which particulate OC represented > 20 % of bulk OC. Nevertheless, our results are in line with Bischoff et al (2016), who reported that a maximum of 10 % OC was present as particulate OC in the Chernozems and Kastanozems of the Kulunda steppe.…”
Section: Partitioning and Composition Of Soil Om In Functionally Diffcontrasting
confidence: 89%
“…However, in the semiarid soils of the studied transect, particulate OC contributed < 10 % of bulk OC, while mineral-bound OC accounted for > 90 % (Table 3). This contrasts with observations from the steppe soils (mostly Chernozems) of European Russia (Breulmann et al, 2014;Kalinina et al, 2011), Canada (Plante et al, 2010), and China (Steffens et al, 2010) in which particulate OC represented > 20 % of bulk OC. Nevertheless, our results are in line with Bischoff et al (2016), who reported that a maximum of 10 % OC was present as particulate OC in the Chernozems and Kastanozems of the Kulunda steppe.…”
Section: Partitioning and Composition Of Soil Om In Functionally Diffcontrasting
confidence: 89%
“…This general trend can be explained by the zonal structure of organic accretions on mineral surfaces, as previously suggested by Kleber et al (2007). The preferential sorption of protein compounds (with small C:N ratio and a large (Kondo et al, 2010); Typic Cryoboralf (Plante et al, 2010); Haplocambid (Grasset et al, 2009); Natrixeralf (Golchin et al, 1994a); Hapludalf (Golchin et al, 1994a); Chromustert (Golchin et al, 1994a); Pellustert (Golchin et al, 1994a); Victoria Grey Clays (Golchin et al, 1994b); Acidic Dystric Cambisol (Hatton et al, 2011); Acidic Glossalbic Cambisol (Hatton et al, 2011) ; Pachic Xerumbrept (Castanha et al, 2008); Ultic Haploxeralf (Castanha et al, 2008). Soil taxa refer to either WRB or Soil Taxonomy.…”
Section: Relationship With a Multi-layer Sorption Modelsupporting
confidence: 68%
“…Filled markers correspond to the soil disaggregated by sonication and open markers correspond to the soil processed by manual agitation. The different soil types reported here are: Andic Dystrudept (Sollins et al , 2009); Inceptic Hapludox (Sollins et al , 2009); Typic Hapludalf (Sollins et al , 2009); Inceptisol (Sollins et al , 2009); Vermic Haplumbrept (this study); Feralsol (Basile‐Doelsch et al , 2009); Hydric Andosol (De Junet, 2008); Andosol (De Junet, 2008); Cambisol (De Junet, 2008); Dystric Cambisol (Kondo et al , 2010); Typic Cryoboralf (Plante et al , 2010); Haplocambid (Grasset et al , 2009); Natrixeralf (Golchin et al , 1994a); Hapludalf (Golchin et al , 1994a); Chromustert (Golchin et al , 1994a); Pellustert (Golchin et al , 1994a); Victoria Grey Clays (Golchin et al , 1994b); Acidic Dystric Cambisol (Hatton et al , 2011); Acidic Glossalbic Cambisol (Hatton et al , 2011); Pachic Xerumbrept (Castanha et al , 2008); Ultic Haploxeralf (Castanha et al , 2008). Soil taxa refer to either WRB or Soil Taxonomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect might be greater in coarser soils than in fine textured ones (Alvarez, 2005). The difference between soil organic matter quality (Plante et al, 2010) and initial soil organic matter content at both site might also influence the increase of soil C and N storage (Malhi et al, 2011a,b;Nyborg et al,1995;Campbell et al,1991Campbell et al, ,1997. Another reason might be attributable to the greater increase of crop residue C and N input by N fertilization when soil fertility was low (Malhi et al, 2011a,b).…”
Section: Nitrogen Fertilization and Tillage Reversal Increased Toc Anmentioning
confidence: 96%